A Endothelial cell nitric oxide bioavailability and insulin sensitivity are regulated by IGF-1 and insulin receptor levels. (9th June 2011) - Abbas, A; Viswambharan, H; Imrie, H; Rajwani, A; Kahn, M; Gage, M; Cubbon, R; Surr, J; Wheatcroft, S; Kearney, M
Abstract : Background: In a similar manner to insulin, the growth promoting hormone Insulin-like Growth Factor-1 (IGF-1), may be an important regulator of endothelial nitric oxide (NO) bioavailability. We have previously reported evidence of increased basal NO production in the vasculature in two murine models of reduced IGF-1 receptor (global hemizygous knockout (IGFRKO) and endothelial cell specific IGF-1R knockout (ECIGFRKO)). Augmentation of this increase in NO is relative to progressive decrease in IGF-1R number (WT vs ECIGFRKO hemizygotes p=0.01, WT vs ECIGFRKO homozygotes p=0.001). Furthermore, by decreasing IGF-1R numbers in the insulin resistant hemizygous insulin receptor knockout (IRKO) model (IRKO × IGFRKO) we have shown insulin sensitivity in the vasculature can be restored. In this study, we have investigated further these receptor interactions with the generation of a mouse overexpressing the human IGF-1R specifically in the endothelium under control of the Tie-2 promoter-enhancer (hIGFREO), and by targeted knockdown of the IGF-1R in human umbilical vein endothelial cells (HUVECs). Methods: Metabolic function was assessed in mice by tolerance tests using whole-blood micro-sampling after insulin or glucose intraperitoneal injection. Cardiovascular function was assessed by thoracic aortic vasomotion ex vivo in the organbath. Complimentary in vitro studies were conducted by siRNA mediated downregulation of the IGF-1 receptor in HUVECs with and wihout insulin stimulation. Nitric oxide synthase activity was measured using an assay measuring conversion of [14C]-L-arginine to [14 C]-L-citrulline. Results: Glucose and insulin tolerance testing showed no difference between hIGFREO mice and wild-type (WT) littermates. Murine thoracic aorta from hIGFREO mice were hypercontractile to phenylepherine (PE) compared to WT (Emax hIGFREO=0.91±0.045 g; WT=0.62±0.045 g, p=0.0036) with decreased response to LNMMA (Emax hIGFREO=47.70±9.87 g; WT=106.1±30.10 g, p=0.048). These data indicate reduced endothelial NO bioavailability in hIGFREO mice compared to WT. HUVECs transfected with IGF1R-siRNA showed increased basal and insulin mediated eNOS phosphorylation in the presence of insulin (Ins: 164±4.9% vs siRNA+Ins: 192±0.7%, p<0.05). eNOS activity (L-arginine, L-citrulline assay) was enhanced upon transfection with IGF1R-siRNA (Scrambled siRNA: 95.7±13.7% vs IGF1R-siRNA: 188.7±48.3%, p<0.05). Implications: These data demonstrate that increasing numbers of IGF-1R specifically in murine endothelium leads to reduced NO bioavailability. Complementary siRNA studies confirm results of previous murine studies that reducing IGF-1R numbers enhance NO bioavailability. Therefore this raises the intriguing possibility that manipulation of IGF-1R numbers may represent a novel therapeutic strategy by which to modify vascular NO bioavailability and endothelial cell insulin sensitivity.